Effectiveness of Privacy Features on the 'X' Social Media Application Platform - Dimas Budi Wibowo ISKANDAR; Ikhwan Difa' Ahmad Purba; Muhammad Zaib; Supina Batubara (Yayasan Sinergi Multidimensi Kreatif, 2024)
The development of information and communication technology has brought major changes to people's lives, including in the way they communicate and interact. One example is the emergence of social media application platforms that allow users to connect with other people, share information and build communities. However, on the other hand, social media application platforms also raise concerns regarding user data privacy. Users are often unaware of how their data is collected, used and shared by social media application platforms. This can pose a risk of data misuse, such as identity theft, fraud and cyberbullying. To address these concerns, many social media application platforms provide privacy features that allow users to control how their data is used. These privacy features can include profile privacy settings, data access controls, and data sharing options. This paper aims to analyze the effectiveness of privacy features on social media application platforms. This paper will discuss the types of privacy features available, how they work, and how effective they are in protecting user data. This paper will also discuss several case studies related to data privacy violations on social media application platforms.